HUBUNGAN PERDAGANGAN INDONESIA DAN THAILAND (STUDI KASUS IMPOR BERAS INDONESIA DARI THAILAND TAHUN 2020-2023) - Gultom, Brayen Jalesveva; Iskandar, Irwan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
Rice is an important commodity in Indonesia's food security and economy, with a high dependence on imports, especially from Thailand. This study aims to analyze the role of rice in Indonesia's food security and economy, factors that drive rice imports, and its impact on Indonesia's food security. This study uses the theory of imports and food security. This theory explains how trade policies and international market dynamics affect the availability, access, and stability of rice supply in Indonesia. The method used in this study is a descriptive qualitative approach with literature studies and policy analysis. The data studied include import policies, bilateral trade agreements, and trends in rice production and consumption in Indonesia and Thailand, to understand the factors that influence import policies and their impact on food security. The results of the study show that Thailand's rice import policy contributes to meeting national food needs, especially in maintaining the availability and stability of domestic rice supplies. Imports are a strategic solution to the imbalance between domestic production and consumption that continues to increase due to population growth, climate change, and land conversion. However, the high volume of imports without data-based planning has a negative impact on local farmers, especially when imports are carried out at the same time as the domestic harvest season. This depresses grain prices, reduces farmer incomes, and threatens the sustainability of the agricultural sector. Therefore, although imports from Thailand are effective in the short term, a sustainable food security strategy requires synergy between trade policies and strengthening national production. Keywords: Rice Import, Thailand, Food Security, Economy, Bilateral Trade